Mechanism and clinical evidence of immunotherapy in allergic rhinitis - De Carli, Marco; Capezzali, Eleonora; Tonon, Silvia; Frossi, Barbara (Frontiers in Allergy, 2023)
Allergic rhinitis is a common upper airway disease caused by hypersensitivity to various aeroallergens. It causes increased inflammation throughout the body and may be complicated by other otolaryngological pathologies such as chronic hyperplastic eosinophilic sinusitis, nasal polyposis, and serous otitis media. Allergic rhinitis is an IgE-mediated disease and immunotherapy can be a possible approach for patients to limit the use of antihistamines and corticosteroids. There is evidence that allergen immunotherapy can prevent the development of new sensitizations and reduce the risk of later development of asthma in patients with allergic rhinitis. However, some patients do not benefit from this approach and the efficacy of immunotherapy in reducing the severity and relapse of symptoms is still a matter of debate. This review highlights new aspects of allergic rhinitis with a particular focus on the impact of sexual dimorphism on the disease manifestation and efficacy to the allergen specific immunotherapy.